Historical survey of teacher education in Brazil in the '30s to the '90s: legislation and educational policies - Maria Teresa Sokolowski (Universidade Estadual Paulista Júlio de Mesquita Filho, 2015)
This article seeks to reconstruct the history of teacher education in Brazil, from the 1930s to the 1990s, the undergraduate programs focused on teacher training for the second phase of what we call today's elementary and high school, emphasizing the legal foundation and political relations, to understand the pedagogical models adopted for the training of these teachers were, historically, responses to the demands of the workplace. The choice to initiate the study of this decade due to the fact that this period was that the universities have instituted the graduation. Then the analysis will be the 1960 and 1970, during the promulgation of LDB 1961 and the implementation of the technicist model of education, ending with the model of teacher training based on the LDB 1996.